Ultra‐deep desulfurization of mercaptan by cyclic selective adsorption‐reactive regeneration at room temperature. Issue 5 (24th January 2022) - Yang, Cuiting; Miao, Guang; Sarbacker, Eric; He, Haoran; Dong, Lei; Wu, Bowen; Li, Guoqing; Janik, Michael J.; Xiao, Jing
Abstract: A cyclic process of selective adsorption‐reactive regeneration over bifunctional Z‐sorb was proposed for desulfurization of heavy mercaptan from gasoline under ambient conditions. A pronounced adsorption capacity (25.7 mg‐S/g‐adsorbent) and selectivity (206.1, 10 times over 1‐hexene) of heptanethiol over bifunctional Z‐sorb were achieved, which can be attributed to the strong adsorbate–adsorbent interaction calculated as high as −44.6 kJ/mol. Catalytic reactive regeneration was proposed to remove stubbornly adsorbed heptanethiol, which achieved complete recovery of Z‐sorb in multiple cycles under room temperature. With the aid of minor H2 O2, the strongly adsorbed heptanethiol in the form of metal‐thiolate (Zn‐SR) transformed to readily desorbed disulfide, which was elucidated via the combined experiment and density functional theory calculations. The developed process provides insights to resolve the trade‐off between adsorption selectivity and regenerability, paving the way for energy‐efficient industrial adsorptive de‐mercaptan of gasoline.